Comparison of reading comprehension in students of 1st and 2nd year of high school of public and non-public schools in Lima Metropolitana - Delgado Vásquez, Ana (2007)
Objectives: a. To study the reading comprehension development on first to secong grade  high school students. b. To analize the comprehension developmental level of first and second grade high school students considering public and private schools...